Combination of formal logic and hedge algebra to estimate the degree of trust - Nguyen, Manh Hung (Journal of Computer Science and Cybernetics, 2015)
Trust plays a more and more important role in many fields of computer sciences such as ambient intelligence, interaction human - machine, affective computing, etc. This paper firstly constructs a logical framework to represent the qualitative aspect of trust/distrust based on a logic of belief, a logic of time, and dynamic logic. Secondly, the paper constructs a hedge algebra and its extension with fuzzy logic to represent the quantitative aspect of trust/distrust and that of their cognitive factors. Then these two aspects are combined to estimate the degree of trust/distrust based on the degree of their cognitive factors.